2020
DOI: 10.4049/jimmunol.2000848
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fusion of IL-10 Engineered to Traffic across Intestinal Epithelium to Treat Colitis

Abstract: IL-10 is a potent anti-inflammatory cytokine capable of suppressing a number of proinflammatory signals associated with intestinal inflammatory diseases, such as ulcerative colitis and Crohn's disease. Clinical use of human IL-10 (hIL-10) has been limited by anemia and thrombocytopenia following systemic injection, side effects that might be eliminated by a gut-restricted distribution. We have identified a transcytosis pathway used by cholix, an exotoxin secreted by nonpandemic forms of the intestinal pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
(52 reference statements)
0
24
0
Order By: Relevance
“…However, the longer efficacy and safety of Mongerson for IBD treatment still need further investigation. IL-10 is a kind of proinflammatory cytokine that can decrease a number of proinflammatory signals associated with IBD (233). However, the application of IL-10 has been limited by some side effects (e.g., anemia and thrombocytopenia) and gut-restricted distribution.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the longer efficacy and safety of Mongerson for IBD treatment still need further investigation. IL-10 is a kind of proinflammatory cytokine that can decrease a number of proinflammatory signals associated with IBD (233). However, the application of IL-10 has been limited by some side effects (e.g., anemia and thrombocytopenia) and gut-restricted distribution.…”
Section: Othersmentioning
confidence: 99%
“…AMT-101 is a chimera produced by genetically fusing non-toxic fragment of cholix to human IL-10 (233). AMT-101 can efficiently cross the epithelial barrier and selectively activate human IL-10 receptors in the intestinal lamina propria (233), which allows IL-10 to play a targeted anti-inflammatory role without causing systemic side effects. Further clinical studies are needed to evaluate the efficacy and safety of AMT-101 for IBD treatment.…”
Section: Othersmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2), an inducible enzyme, drives inflammation and has been found to be highly expressed in patients with IBD ( Nair et al., 2011 ). Interleukin-10 (IL-10), a potent anti-inflammatory cytokine, is capable of suppressing a number of proinflammatory signals associated with intestinal inflammatory diseases, such as ulcerative colitis and Crohn’s disease ( Fay et al., 2020 ). Previous studies have reported that CB administration reduced inflammatory cytokines, including IL-1ÎČ, IL-6, COX-2, and TNF-α, while increased IL-10 expression levels in colon tissue ( Hagihara et al., 2020 ; Liu et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Biologic therapies aiming to treat IBD via the oral route have been reported at various stages of development [53][54][55][56][57][58] . However, V56B2 is unique in that it is the first orally delivered intestinal protease resistant bispecific antibody to provide dual inhibition of two key, clinically validated, IBD pathways without systemic immunosuppression.…”
Section: Discussionmentioning
confidence: 99%